Impacts of Central Tropical Pacific SST on the Reversal of December and January Surface Air Temperature Anomalies Over Central Asia - Li, Haishan; Fan, Ke; Li, Hua; Xu, Zhiqing (Frontiers in Earth Science, 2022)
The reversal of winter surface air temperature anomalies (SATAs) over Central Asia (CA) between December and January is investigated in this study and found to be closely related to the sea surface temperature anomalies (SSTAs) over the central tropical Pacific (CTP). The cool CTP SSTAs can lead to positive (negative) SATAs over CA in December (January). The different responses of SATAs over CA to the SSTAs are attributed to different Rossby wave propagations. In December, a wave train from the North Pacific directly reaches CA, while in January it mainly propagates in the meridional direction and cannot reach CA. The January SATAs of CA are influenced by a wave train from the North Atlantic, which is induced by CTP SSTAs indirectly. The wave trains from the North Pacific are mainly driven by the Gill-type response to the cool CTP SSTA in both December and January. In January, since the climatological subtropical jet stream over the North Pacific is stronger and situated more towards the equator, a stronger Gill-type response is excited and causes the meridional propagation of the Rossby waves. Then, this stronger Gill-type response can cause strong zonal wind anomalies over the East Pacific. Local anomalies of the synoptic-scale transient eddy can be further caused by the zonal wind anomalies and travel eastward to the North Atlantic. The eddy-induced geopotential anomalies over the North Atlantic can further trigger Rossby waves and cause the negative SATAs over CA. Numerical simulations reproduce these mechanisms.